Literary correspondences: Bernardin de Saint-Pierre and Mme de Genlis - Ford, Rebecca L. (Edinburgh University Press, 2015)
Although Bernardin’s correspondence spans most of his adult life and involves a wide range of correspondents and subject matter, there is a marked increase in the number of correspondents and frequency of correspondence from the time he begins to enjoy real literary success. Indeed, the relationship between the reading and writing of letters and the writing and reading of Bernardin’s published works is a close and multi-faceted one. The focus for this article is the correspondence between Bernardin and Mme de Genlis, one of the most significant literary figures in Bernardin’s correspondence network. Their correspondence casts light on Bernardin’s place in late eighteenth-century literary and cultural life and his developing identity as an author. Bernardin’s correspondence with Mme de Genlis helps him to deal with practical issues surrounding the publication of his works, and to explore the moral and ethical implications of authorship; but it also reveals the difficulties inherent in the act of correspondence itself.